Sphingosine‐1‐phosphate inhibits IL‐1‐induced expression of C‐C motif ligand 5 via c‐Fos‐dependent suppression of IFN‐β amplification loop. Issue 12 (5th August 2015) - Yester, Jessie W.; Bryan, Lauren; Waters, Michael R.; Mierzenski, Bartosz; Biswas, Debolina D.; Gupta, Angela S.; Bhardwaj, Reetika; Surace, Michael J.; Eltit, Jose M.; Milstien, Sheldon; Spiegel, Sarah; Kordula, Tomasz
ABSTRACT: The neuroinflammation associated with multiple sclerosis involves activation of astrocytes that secrete and respond to inflammatory mediators such as IL‐1. IL‐1 stimulates expression of many chemokines, including C‐C motif ligand (CCL) 5, that recruit immune cells, but it also stimulates sphingosine kinase‐1, an enzyme that generates sphingosine‐1‐phosphate (S1P), a bioactive lipid mediator essential for inflammation. We found that whereas S1P promotes IL‐1‐induced expression of IL‐6, it inhibits IL‐1‐induced CCL5 expression in astrocytes. This inhibition is mediated by the S1P receptor (S1PR)‐2 via an inhibitory G—dependent mechanism. Consistent with this surprising finding, infiltration of macrophages into sites of inflammation increased significantly in S1PR2 –/– animals. However, activation of NF‐κB, IFN regulatory f actor‐1, and MAPKs, all of which regulate CCL5 expression in response to IL‐1, was not diminished by the S1P in astrocytes. Instead, S1PR2 stimulated inositol 1, 4, 5‐trisphosphate‐dependent Ca ++ release and Elk‐1 phosphorylation and enhanced c‐Fos expression. In our study, IL‐1 induced the IFNβ production that supports CCL5 expression. An intriguing finding was that S1P induced c‐Fos‐inhibited CCL5 directly and also indirectly through inhibition of the IFN‐β amplification loop. We propose that in addition to S1PR1, which promotes inflammation, S1PR2 mediates opposing inhibitory functions that limit CCL5 expression and diminish the recruitment of immune cells.—Yester, J. W., Bryan, L., Waters, M. R., Mierzenski, B., Biswas, D. D., Gupta, A. S., Bhardwaj, R., Surace, M. J., Eltit, J. M., Milstien, S., Spiegel, S., Kordula, T. Sphingosine‐1‐phosphate inhibits IL‐1‐induced expression of C‐C motif ligand 5 via c‐Fos‐dependent suppression of IFN‐β amplification loop. FASEB J. 29, 4853–4865 (2015). www.fasebj.org